Maternal antihypertensive medication use and selected birth defects in the National Birth Defects Prevention Study. Issue 19 (10th September 2018) - Fisher, Sarah C.; Van Zutphen, Alissa R.; Werler, Martha M.; Romitti, Paul A.; Cunniff, Christopher; Browne, Marilyn L.; ,
Abstract : Background: There are limited data on the relationship between antihypertensive medication use in early pregnancy and risk of birth defects. Methods: Using data from the National Birth Defects Prevention Study, we examined associations between specific antihypertensive medication classes and 28 noncardiac birth defects. We analyzed self‐reported data on 17, 038 case and 11, 477 control pregnancies with estimated delivery dates during 1997–2011. We used multivariable logistic regression to estimate odds ratios (ORs) and 95% confidence intervals, adjusted for maternal age, race/ethnicity, body mass index, parity, pregestational diabetes, and study site, for associations between individual birth defects and antihypertensive medication use during the first trimester of pregnancy. We compared risk among women reporting early pregnancy antihypertensive medication use to normotensive women. Results: Hypertensive women who reported early pregnancy antihypertensive medication use were more likely to be at least 35 years old, non‐Hispanic Black, obese, multiparous, and to report pregestational diabetes than normotensive women. Compared to normotensive women, early pregnancy antihypertensive medication use was associated with increased risk of small intestinal atresia (adjusted OR 2.4, 95% CI 1.2–4.7) and anencephaly (adjusted OR 1.9, 95% CI 1.0–3.5). Risk of these defects was not specific to any particular medication class. Conclusions: Maternal antihypertensive medication use was not associated with the majority of birth defects we analyzed, but was associated with an increased risk for some birth defects. Because we cannot entirely rule out confounding by the underlying hypertension and most ORs were based on small numbers, the increased risks observed should be interpreted with caution.